Stock Liquidity and Stock Price Crash Risk - Chang, Xin; Chen, Yangyang; Zolotoy, Leon (Journal of financial and quantitative analysis, 2017)
We find that stock liquidity increases stock price crash risk. To identify the causal effect, we use the decimalization of stock trading as an exogenous shock to liquidity. This effect is increasing in a firm’s ownership by transient investors and nonblockholders. Liquid firms have a higher likelihood of future bad earnings news releases, which are accompanied by greater selling by transient investors, but not blockholders. Our results suggest that liquidity induces managers to withhold bad news, fearing that its disclosure will lead to selling by transient investors. Eventually, accumulated bad news is released all at once, causing a crash.